Unconventional resistance under the land bank agency regime in agrarian conflicts - Satrio Wahyu Nugroho (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: The land bank agency, a product of the Job Creation Law, has eclipsed any hope of resolving agrarian conflicts in Indonesia. Various resistances against arbitrary land claims by indigenous communities continue, complemented by unconventional forms of resistance to achieve justice. Using the perspective of unconventional resistance or everyday resistance introduced by Scott, the author attempts to highlight how communities struggle through avenues other than legal channels in agrarian conflicts against the Land Bank Agency. Methods: This study employs a qualitative normative approach, drawing on secondary sources to analyse agrarian law, the Land Bank Agency, and related legal conflicts before and after its establishment in Indonesia. Findings: With the support of various references, this study finds that non-conventional resistance against the Land Bank Agency in agrarian conflicts has similar or more severe challenges than agrarian conflicts in the regime before the Land Bank Agency. The presence of the Land Bank Agency further exacerbates the situation with strong legal legitimacy to carry out land grabs and unilateral claims to land. All of this is intended for national development ideals supported by private investment. Conclusion: Non-conventional resistance from indigenous communities against the Land Bank Agency faces new challenges where indigenous communities are increasingly difficult to achieve their goals and are increasingly easy to criminalize in the process of fighting for land control rights. Novelty/Originality of this article: This study highlights something that has not previously been prioritized in research on the Land Bank Agency, namely the results of community reactions to conflicts involving the Land Bank Agency. Specifically, the author tries to show how the results of non-conventional community resistance in agrarian conflicts under the Land Bank Agency regime.